(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to improve the insurance service through the marketing commission as a tool that enables the insurance companies to achieve a competitive advantage. The researcher, by observing the challenges faced by insurance companies, insurance agents and brokers, raised the main question of the research: Is there an effect of the marketing commission on the competitive advantage of insurance companies? The data was obtained through the financial statements and annual reports of the research sample companies (the National General Insurance Company, the Iraqi General Insurance Company, Al-Hamra Private Insurance Company, Dar Al-Salam Private Insurance Company) from the managers of the financial department of the companies, and the data was analyzed using statistical methods (arithmetic mean standard deviation and coefficient of difference) and the relationship between the research variables was tested using the normal distribution test model of the variables (Kumlikov-Smirnov) and the statistical program (SPSS 23), and after analyzing the data, the research concluded that there is a significant statistically significant effect of the marketing commission on the competitive advantage in the insurance company Iraqi General and Dar Al-Salam Private Insurance Company